CLT-concrete composite floors with notched shear connectors. (20th January 2019) - Jiang, Yuchen; Crocetti, Roberto
Highlights: Experiments were performed on notched connections and CLT-concrete composite floors. Analytical method based on γ-method is suitable for CLT-concrete composite floors. 3D FE-models for notches and composite floors were developed and validated. Influence of notch depth on connections and composite floors were investigated. Abstract: The aim of the paper is to gain data on the mechanical behaviour of CLT-concrete composite floors and subsequently to check if commonly adopted analysis methods are suitable for this particular type of structure. The studies are conducted through laboratory tests, analytical models and numerical modelling. In the shear tests, the notched connections presented considerable stiffness and shear capacity, and failed eventually with shear fracture in the concrete. The bending test results showed that the CLT-concrete composite floors with notched connections had a very high composite action. At the moment of failure, all notched connections along the span remained nearly undamaged, and only one fine concrete crack appeared at the notch near the support. The paper also presents a theoretical calculation method based on the well-known γ-method, which is suitable for CLT-concrete composite floors. In particular, for the composite floors with 5-layer-CLT panel, a model using a combined distributed stiffness is introduced to take account of the stiffness of both the mechanical fasteners and the CLT's cross layer, which extends the validity range of the γ-method to composite systems made of CLT panels with more than three layers. Three-dimensional FE-models for CLT-concrete notched connections and for composite floors are developed using the commercial finite element programme ABAQUS. With the FE-models calibrated with experimental results, parametric studies are conducted to investigate the influence of the notch depth on the mechanical performance of both notched connections and CLT-concrete composite floors. It is concluded that the stiffness of notched connections increases linearly with the depth of the notch, while it is not this case for the shear capacity. The variation of notch depth within the investigated range, i.e. 15 mm to 35 mm, is found to have no significant influence on the load-deflection response of composite floors.